Protocol for a scoping review investigating success in research capacity building for nurses, midwives and allied health professionals - Colin Hamilton; Alexandra Malyon; Natalie Pike; Lok Yiu Wong; Kieran Lock; Emma Jones; Gabrielle Deora; Graham Martin; Joanne McPeake (PLoS ONE, 2025)
Objective To identify and describe how success is currently conceptualised in research capacity building in nurses, midwives and allied health professionals in the UK. Introduction Having a research active healthcare workforce is associated with improved patient outcomes as well as staff retention. It is therefore seen as a key target for many healthcare organisations. Nurses, Midwives and Allied Health Professionals form the largest group of healthcare professionals but are traditionally less involved in research than medically trained staff. A variety of schemes have aimed to address this through so called “research capacity building” activities but an understanding of what constitutes success is needed to aid development of future interventions. Inclusion criteria Participants - Any or all of Nurses, Midwives or Allied Health Professionals. Concept- Definition of success or description of aims of activities aimed at research capacity building. Context- Within in the UK. Methods Content from peer reviewed journals will be searched for in: Embase, CINAHL, MEDLINE, AMED, BNI and EMCARE Web of Science Core Collection. Grey Literature will be searched for in Google and Overton as well as key websites of organisations that work in developing research capacity. Website searches will include National Institute for Health and Care Research, all charities that form the Association of Medical Research Charities as of search date and the websites for the recognised professional bodies for Nurses, Midwives and Allied Health Professionals. Screening of titles and abstracts then full text will be undertaken by one person with 20% cross checked by a second reviewer. Data extraction will use a bespoke data extraction tool and will be undertaken by one person, with 20% cross checked with a second reviewer. A narrative synthesis and qualitative content analysis will be used to synthesise the data. Registered OSF Registries: https://doi.org/10.17605/OSF.IO/QVCDX